2007
DOI: 10.1002/cphc.200600496
|View full text |Cite
|
Sign up to set email alerts
|

In Situ SAXS/WAXS of Zeolite Microwave Synthesis: NaY, NaA, and Beta Zeolites

Abstract: A custom waveguide apparatus is constructed to study the microwave synthesis of zeolites by in situ small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS). The WR-284 waveguide is used to heat precursor solutions using microwaves at a frequency of 2.45 GHz. The reaction vessels are designed to include sections of thin-walled glass, which permit X-rays to pass through the precursor solutions with minimal attenuation. Slots were machined into the waveguide to provide windows for X-ray energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…A custom-built microwave reactor was used to monitor MWR-assisted silicate zeolite synthesis. 48,49 This reactor operated at 2.45 GHz and featured a rectangular waveguide, coaxial stub tuners, and a sliding short (Fig. 5).…”
Section: B In Situ Small-and Wide-angle Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…A custom-built microwave reactor was used to monitor MWR-assisted silicate zeolite synthesis. 48,49 This reactor operated at 2.45 GHz and featured a rectangular waveguide, coaxial stub tuners, and a sliding short (Fig. 5).…”
Section: B In Situ Small-and Wide-angle Scatteringmentioning
confidence: 99%
“…This experimental setup was then used to study the role of precursor solution on silicate zeolite synthesis. 49 Panzarella et al found that MWR enhanced the rate of zeolite crystallization regardless of the precursor used. Despite the rate increase, certain precursor concentrations had no effect on the mechanisms of zeolite formation, as SAXS data indicated that the nanoparticle reorganization leading to crystallization is similar.…”
Section: B In Situ Small-and Wide-angle Scatteringmentioning
confidence: 99%
“…The crystallization was found to be significantly accelerated by the exposure of synthesis gels to microwave radiation. Thereafter, microwave heating synthesis has been applied for the synthesis of a number of zeolites, including zeolite A (LTA) (Panzarella et al, 2007;Slangan et al, 1997 (a)), faujasite (FAU) (Panzarella et al, 2007;Srinivasan & Grutzeck, 1999), analcime (ANA) and Gobbinsite (GIS) (Sathupunya et al, 2002), beta (BEA) (Panzarella et al, 2007), ZSM-5 (MFI) (Phiriyawirut et al, 2003;Somani et al, 2003), silicalite-1 (MFI) (Hu et al, 2009), AlPO 4 -5 (AFI) , VPI-5 (VFI) (Carmona et al, 1997), and cloverite (CLO) (Park & Komarneni, 2006). The number of publications of microwave heating synthesis of zeolite increases year by year.…”
Section: Zeolite and Zeolite-like Porous Molecular Sievesmentioning
confidence: 99%
“…Although in situ Small Angle X-ray Scattering (SAXS) and Wide Angle X-ray Scattering (WAXS) has been applied to track zeolite formation by many authors [9,10,11,12,13], in situ SAXS and WAXS has only been applied in a limited way to the early kinetics studies of metakaolin geopolymers [14]. …”
Section: Introductionmentioning
confidence: 99%